What science means to me: Understanding personal identification with (evolutionary) science using the sociology of (non)religion. (August 2020) - Jones, Stephen H.; Elsdon-Baker, Fern; Catto, Rebecca; Kaden, Tom
Within science and technology studies, there is an established tradition of examining publics' knowledge of, trust in, access to and engagement with science, but less attention has been paid to whether and why publics identify with science. While this is understandable given the field's interest in bridging gaps between publics and producers of scientific knowledge, it leaves unanswered questions about how science forms part of people's worldviews and fits into cultural politics and conflict. Based on 123 interviews and 16 focus groups with mixed religious and nonreligious publics and scientists in the United Kingdom and Canada, this article utilises approaches from the sociology of (non)religion to delineate varieties of science identification. It maps out 'practical', 'norm-based', 'civilisational' and 'existential' identifications and explores how these interrelate with people's social characteristics. The article illustrates how science identification is typically dependent on a constellation of cultural/political influences rather than just emerging out of interest in science.